Implementation Of Management Standards For MTs An-Nur Palangka Raya In Improving Madrasah Quality - Puspita, Puspita; Ajahari, Ajahari; Misbah, Misbah; Arifin, Anwar; Asmawati, Asmawati; Tejawiani, Ida (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This research examines the implementation of management standards at Mts an-nur Palangkaraya in improving the quality of Madrasah education. The objectives of this study include: To find out the standard management program planning, implementation of standard management programs, monitoring and evaluation of standard management programs at MTS An- nur Palangkaraya. This research uses a qualitative descriptive approach, as Moleong argues